Peranan Green Marketing terhadap Consumer Behavior - Lu, Cen (Zenit, 2014)
Nowadays, environment has become an actual issue in community, government, and business organizations. Environmental conditions are threatening the health and well-being of consumers globally. Consumers have to take the responsibility to support this movement. There are awarenessand motivation of consumers to encourage changes in the markets in which companies begin to manufacture environmentally friendly products that are more economical. Environmental issues have made companies modify the way of doing business to compete in the market and force companies to adapt their strategic planning process in order to meet legal, social, and economic requirements associated with environmental friendly products. In many countries, there are conservation programs to preserve the existing environment. Besides, companies must be disciplined in marketing,developing green marketing ideas, and communicating environmental messages, including environmental health issues. Green marketing is a form of marketing in which production activities, product packaginsg and promotional communications are associated with environmental safety.Hence, they make green culture as a concept of the company value with the aim to minimize the negative impacts on the environment. Green marketing is associated with ethical principles and values prevailing in society. Therefore, companies must be attentive to the heightened awareness ofconsumers to self-care, healthy lifestyle, and environment preservation. Consumer interests to improve the quality of the environment through the consumption of environmentally friendly products have risen significantly. Consumer behavior towards green marketing should be evaluated in terms ofaffective and cognitive. The behavior of consumers who use environmentally friendly products can be interpreted as consumer behavior in which individuals meet their needs, but do not ignore the needs of others in the long run. Media attention and consumer awareness of environmental issues arepresently on the rise. Such Consumer behavior makes companies change their business model in production methods that do not pollute the environment, yet create a more ethical and responsible marketing in developing environmentally friendly products and managing existing environmentalproblems.Keywords: green marketing, consumer behavior